Transition metal complexes of bis(diphenylphosphino)methane, dithizone and dithiolenes: structural, spectroscopic, electrochemical and computational studies - Wewers, Francois (Department of Chemistry, 2016)
A series of heterobi- and tri-metallic complexes were prepared by the metallation of the carbanion derived from [M(CO)₄(dppm)] (M = Cr, Mo or W), [ML(dppm)] (L= dithiolene; M = Pd or Pt), or the cationic precursor, [Ru(Cp)(PPh3)(dppm)]PF₆. The complexes were characterized by ¹H and ³¹P NMR, IR and UV/Vis spectroscopies and X-ray crystallography. The presence of electrochemical communication in these complexes was investigated by means of cyclic voltammetry. Correlation studies of electrochemical potentials and 31P NMR data or carbonyl stretching frequencies of the Group 6 mercurated complexes show that the mercury atom does facilitate the flow of electrons through the four-membered chelate ring. However, this effect has been established to be weak. Similar weak electronic effects were found to exist in the case of the Ru, Pd and Pt complexes. Evidence of "through-space" communication was established to be present in the ferrocenyl derivatives. X-ray crystallographic studies show that mercuration of the carbanion neutralizes the residual electron density in the chelate ring for the chromium bi- and tri-metallic complexes. This was also demonstrated for the cationic ruthenium complex. X-ray crystallographic studies were performed on dithizone and its corresponding salt in an attempt to resolve or explain the often debated tautomerism of this molecule in the solid state and in solution. The structure of the parent molecule showed the co-existence of the two tautomeric forms in a single structure, with a 2:1 preference for the symmetrical keto form, compared to the enol form. DFT calculations have been performed and have been shown to be mutually consistent with structural data, showing a negligible energy difference of 3.1 kcal mol⁻¹ between the two forms. Computational calculations were also performed to investigate the solution characteristics of the dithizonate salt. An analysis of the HOMO and Fukui functions show the sulfur atom to be the most nucleophilic and therefore the preferred site for deprotonation with an energy barrier of 17 kJ mol⁻¹ compared to the nitrogen atom. While the 1H NMR spectrum shows evidence of the existence of proton exchange in solution, we were unable to model this. However, DFT solution studies show that the keto form is most stabilized. A series of palladium and platinum dithizonate complexes, with the general formula, [M(PP)(Hdptc)]X or [M(PP)(dptc)] (PP = mono- or bidentate phosphine ligand; M = Pd or Pt; X = PF₆ or BPh₄), was prepared and investigated for their photochromic behaviour. None of these complexes exhibited any photochromism. X-ray crystal structures of [Pt(COD)(dptc)] and [Pt(dppf)(dptc)] were determined. Both complexes contain the dithizone ligand in a doubly deprotonated, or secondary, form. Synthetic routes to the preparation of mixed dithiolene-dithizone complexes of mercury and platinum were developed. The complexes were characterized by ¹H and ¹³C NMR, IR and UV/Vis spectroscopies and X-ray crystallography. Spectroscopic studies show that the mercury complexes are all photochromic, while the platinum complex showed no photochromism in solution. Electrochemical studies show the absence of rich electrochemical activity for the Hg complexes. The [Pt(mnt)(Hdptc)]⁺ complexes, in contrast, showed greater redox activity. X-ray studies on the analogous complexes, Ph₄As[Hg(mnt)(Hdptc)] and Bu₄N[Pt(mnt)(Hdptc)] revealed an absence of any S···S or Metal···S interactions, often associated with planar sulfur rich ligands.